Banking performance before and during the Covid-19 pandemic: Perspectives from Indonesia - Susanti; Rediyanto Putra; Moh. Danang Bahtiar (Cogent Economics & Finance, 2023)
This study aims to provide empirical evidence regarding the impact of the COVID-19 pandemic on banking performance in Indonesia. This study examines differences in Indonesian banking performance before and during the COVID-19 pandemic. Banking performance in this study was measured using the CAMEL measure. The analysis was carried out by conducting a different test using the SPSS application version 22.0. Based on the results of tests conducted on 205 observations on banking from 2018 to 2021, it was found that the CAR, ROA, ROE, BOPO, LDR, and Customer Deposit levels from banks in Indonesia had a significant difference between before and during the COVID-19 pandemic. However, there was no significant difference between the NPL banking level in Indonesia before and during the COVID-19 pandemic. This proves that the COVID-19 pandemic has harmed banking in Indonesia, so the government must pay attention to the current banking strength to survive and recover after the COVID-19 pandemic.
Keywords: G21; M21; 330; Camel analysis; financial performance; the COVID-19 pandemic